An innovative derivatization‐free IC‐MS/MS method for the detection of bisphosphonates in horse plasma. Issue 10 (14th July 2020) - Garcia, Patrice; Pinètre, Justine; Morel, Sylvain; Jaubert, Murielle; Deruy, Xavier; Perot, Isabelle; Delcourt, Vivian; Loup, Benoit; Popot, Marie‐Agnès; Bailly‐Chouriberry, Ludovic
Abstract: Bisphosphonates are prohibited drugs according to Article 6 of the International Agreement on Breeding, Racing and Wagering of the International Federation of Horseracing Authorities (IFHA) and the International Equestrian Federation (FEI). These compounds are used for the treatment of lameness, navicular and bone diseases in horses and are divided into two groups: non‐nitrogen‐containing bisphosphonate drugs (e.g. clodronic acid) and nitrogen‐containing bisphosphonate drugs (e.g. zoledronic acid). Their hydrophilic properties and the high affinity for the bone matrix make the control of their use quite difficult. Current analytical strategies to detect such compounds often rely on a solid phase extraction (SPE) followed by detection by means of UHPLC–MS/MS after methylation with chemical reagents. To improve the analysis throughput and to eliminate the need for chemical derivatization, an innovative 96‐well SPE followed by ion chromatography‐mass spectrometry was developed. Analyses are conducted on an ICS‐6000 HPIC system coupled to a TSQ Altis™ (Thermo Scientific™). The use of a 96‐well SPE allowed 5‐fold sample increase and a 6‐fold throughput improvement. While preliminary results conducted on horse plasma exhibited similar performances to the method for the detection of non‐nitrogen‐containing bisphosphonates, the analytical performances of nitrogen‐containing bisphosphonates were greatly improved. Abstract : The application of IC‐MS/MS to non‐nitrogen‐containing and nitrogen‐containing bisphosphonates allows their detection without derivatization with excellent performances in terms of sensitivity and specificity. The use of the 96‐well SPE for routine analysis also enables a 6‐fold throughput improvement.